Developmental Psychopathology 2016
DOI: 10.1002/9781119125556.devpsy112
|View full text |Cite
|
Sign up to set email alerts
|

Peer Relations and Developmental Psychopathology

Abstract: Peers provide a context in which child and adolescent development occurs. Peers may right wayward developmental trajectories, buffering the effects of deleterious risk factors. Adverse peer experiences also may distort developmental pathways, contributing to psychopathology. Numerous distinct peer constructs that signal developmental perturbations have been identified and associated with indices of psychopathology. This chapter reviews peer experiences in early childhood (i.e., social withdrawal), school‐age y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
106
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 92 publications
(110 citation statements)
references
References 334 publications
3
106
0
1
Order By: Relevance
“…Given that the current study was able to model change in discrimination over time, it suggests that changes in peer discrimination in the high school period are particularly problematic in their prediction of depressive symptoms. This finding is consistent with past work finding that peer interpersonal stressors influence the development of depressive symptoms (Prinstein & Giletta, in press). …”
Section: Discussionsupporting
confidence: 93%
“…Given that the current study was able to model change in discrimination over time, it suggests that changes in peer discrimination in the high school period are particularly problematic in their prediction of depressive symptoms. This finding is consistent with past work finding that peer interpersonal stressors influence the development of depressive symptoms (Prinstein & Giletta, in press). …”
Section: Discussionsupporting
confidence: 93%
“…For over 50 years, studies of peer relationships have identified the far-reaching influence of adolescents’ offline peer experiences on a variety of critical psychological, educational, behavioral, and physical outcomes (Almquist 2009; Almquist and Östberg 2013; Menting et al 2016; Modin et al 2011). Peer relations researchers have examined numerous peer processes, relationship types, behaviors, and reputations with implications for adolescents’ development and wellbeing (Choukas-Bradley and Prinstein 2014; Furman and Rose 2015; Prinstein and Giletta 2016; Rubin et al 2015). However, as social media becomes a central feature of adolescents’ lives, it is essential to better understand the ways that these peer experiences are shaped by the social media environment.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is likely that, beyond dyadic interactions, social media has unique implications for adolescent’s experiences of group-based peer processes. Thus, in the current paper (Part 2), we expand on our prior work by applying the transformation framework to three broad peer relations constructs with critical implications for adolescent adjustment: peer victimization; peer status, acceptance, and rejection; and peer influence (Choukas-Bradley and Prinstein 2014; Furman and Rose 2015; Prinstein and Giletta 2016; Rubin et al 2015). Although these processes and behaviors may occur within dyadic relationships, they are especially relevant to understanding adolescents’ experiences within the larger peer network.…”
Section: Introductionmentioning
confidence: 99%
“…Particularly in adolescence, forming and maintaining positive social relationships is a key developmental task. During this period in life, social relations are very salient and powerful, and a frustrated need to belong may be particularly harmful for one’s well-being (Prinstein & Giletta, in press). Indeed, feeling lonely—a key indicator of a frustrated need to belong—marks an increased risk for psychopathology and health problems in adolescence (Heinrich & Gullone, 2006).…”
mentioning
confidence: 99%
“…Moreover, the majority of previous work with children or adolescents used pictures or videos of adult faces. Given that differences in neural processing of facial emotions on adult versus adolescent faces have been documented in adolescents (Marusak, Carré, & Thomason, 2013), and given the increased attunement to peers in adolescence (Prinstein & Giletta, in press), this study made use of a recently developed and validated picture set of emotional expressions in adolescents (Egger et al, 2011). …”
mentioning
confidence: 99%